Maxims Analysis in a conversation of Indonesian Movies entitled “Malam Minggu Miko”: A Pragmatics study - Barokah, Nurlaillatul; Sunandar, Muhamad Nandang (Journal of English Education Studies, 2024)
The aim of the research was to identify and describe the maxims that have been violated in the dialogue of “Malam Minggu Miko” movie and also to know the maxim that compliance with. The analysis of maxim was conducted to “Malam Minggu Miko” movie. The writer conducted this analysis based on two research questions about the violation of cooperative principle (maxims) and its offense. In this research analysis, the researcher used qualitative in descriptive as a method. And used “Malam Minggu Miko‟ movie as the subject for her analyses. This research was to analyze the application of Grace‟ cooperative principle (maxims) in the “Malam Minggu Miko” movie. This was analyzed the violation of the maxims, offense and kinds of violation shown in that movie. After the writer analyzed “Malam Minggu Miko” movie from these three factors, it can be concluded that this movie has broken all existing maxim. Besides, this movie are also obeyed several cooperative principle in several dialogue, they are the maxim of quantity and quality. Furthermore, “Malam Minggu Miko” movie has done several kinds of offense; the first kind is violation, where the hearer is unable to use the maxim correctly. The second offense is kind of clash, where the use of maxim conflicting.